Peran Pemerhati Lingkungan Dalam Undang-Undang Nomor 6 Tahun 2023 Tentang Cipta Kerja Terkait Anaslisa Mengenai Dampak Lingkungan (AMDAL) (Studi Wahana Lingkungan Hidup NTB) : The Role Of Environmental Observers In Law Number 6 Of 2023 Concerning Eia-Related Work Creation (Case Study In WALHI NTB) - sintiyakarina_19 (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2023)
This study aims to find out the mechanism for preparing the AMDAL and the existence of the West Nusa Tenggara Environmental Forum (WALHI NTB) as an Environmental Observer based on Law Number 6 of 2023 concerning Job Creation. The type of research used in this research is normative-empirical, namely legal research by looking at the existing regulations related to the practice in the field or with existing facts regarding the problems encountered in this study. The approach methods used in this study are statutory approaches, conceptual approaches and case approaches. The data collection techniques used were interviews and document studies. The mechanism for preparing an EIA in the Job Creation Law is not much different from that in the PPLH Law. The existence of WALHI NTB as an environmental observer in the AMDAL continues even though its participation in the preparation of the AMDAL is not explicitly stated in Law Number 6 of 2023 Concerning Job Creation. right to get a good and healthy environment.